First identification and characterization of porcine enterovirus G in the United States - Anbalagan, Srivishnupriya; Hesse, Richard A.; Hause, Benjamin M. (My University, 2014)
Porcine enterovirus G (EV-G) is a member of the family Picornavirdae, genus Enterovirus. To date, eleven EV-G types (EV-G1 through EV-G11) have been identified in pigs from Asia and Europe however they have never been reported in North America. In this study, we isolated and characterized the complete genome of NP/2013/USA, an EV-G from a porcine diarrhea sample from the United States. The complete genome consists of 7,390 nucleotides excluding the 3′ poly(A) tail, and has an open reading frame that encodes a 2,169 amino acid polyprotein. NP/2013/USA was most similar at the nucleotide (84%) and amino acid (95%) level to the HM131607, an EV-G1 type isolated from China in 2012.
Keywords: Porcine enterovirus G